Esterification of oleic acid with ethanol catalysed by 12-tungstophosphoric acid supported on alumina - Che Norrizuan, Che Abdul Rahim (2012)
Ester of organic acids and alcohols form an industrially important class of substances.They are mainly produced as components of esterification reactions.Esterification as well as transesterification reactions has been largely applied to the production of biodiesel,which may be defined as alkyl esters of long chain fatty acids derived from renewable resources such as biomass.This work presents an impregnation route to support 12-Tungstophosporic Acid (H3PW)on Alumina (Al2O3)in acidic aqueous solution(HCl 0.1 mol/L)at different ratios(5, 10, 15, 25, 40 and 60 wt%).The catalyst were further applied in the esterification of oleic acid with ethanol.The samples calcined at 200°C for 4 h were characterized by Fourier Transform Infrared Spectrosocy (FTIR),X-ray Diffraction(XRD)and Thermogravimetric Analysis (TGA).The effect of the most relevant variables of the process such as ratio of catalyst (H3PW/Al2O3) and reaction temperature was investigated in the present study.An optimum reaction performance,80% of oleic acid conversion was achieved at 25 wt% catalyst loading,60°C,4 h reaction and 1:6(oleic acid:ethanol)molar ratio.Studies show that the catalyst is feasible to be used for biodiesel production